(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Premature graying may be due to early depletion of melanocyte reservoir seeding potential owing to environmental factors, inflammation or psychological stress. Reactive oxygen species-mediated damage to mitochondrial and nuclear DNA with mutations with age and dysregulation of anti-oxidant mechanisms or pro/anti-apoptotic factors within the cells results in melanocytic aging. Ayurveda addresses canities as Palithya. Bhrajaka pitha is responsible for imparting natural colour to hair. Ayurveda classics mention it as Sirogatavyadhi (Caraka Samhita), Sirokapalagatavyadhi (Vagbhata) or Khudraroga (Sushruta Samhita). Case presentation: The patient was of age 28 years, female, unmarried moderately built with BMI 21.8, with history of PCOD and migraine. She had presented with greying of hair over vertex region of head. She was of Kaphapitha prakrthi with dietary habits including fast food, spicy food, pickles and mixed diet. She had stress due to work and due to going to work by scooter, she is prone to sunlight exposure and had a habit of helmet wearing. She was given internal medication of Guluchyathi kashayam, Usheerasavam and Chandraprabha vati. Then, she was given Vicharana snehapana with Mahathikthaka ghrta and done Shodhana with Avipathi choornam. Then the Bahya prayoga of Siropichu was done with Prapoundarikadi taila and Rasayana done with Agasthya rasayana. Conclusion: Guluchyathi kashayam, Usheerasavm and Chandraprabha caused balance of Agni in the body, they were Pithasamaka also. Mahatikthaka snehapana reduced dryness and brought Snighdada to the body. The accumulated imbalanced Pitha was eliminated from the body through Virechana by Avipathy choornam. After Shodana, external application as Siropichu with Prapoundarikadi taila which was Palithyahara, Pithahara and Keshya was done. Rasayana was given with Agasthya rasayana. The new hair growth was of black, there was an increase in hair growth and satisfactory reduction in hair fall. There was stress relief and overall coolness of body.